Models of Marginality in the Historical-Theoretical and Political-Legal Contexts - Faritovna Stepanenko, Raviya; Nailjevna Ainoutdinova, Irina; Anatolyevich Romashov, Roman (Cuestiones Políticas, 2020)
The research analyzes different models of marginality in historical-legal and political-legal contexts. The relevance of the study is due to the significant risks of spreading marginality in modern society, as a prerequisite for legal anomia. Understanding marginality, as one of the destructive forms of legal awareness and legally significant limiting behavior, allows marginality to be modeled historically and theoretically in relation to sociocultural phenomena such as state and law. At the methodological level, documentary design was used close to historical research and epistemological reflection typical of interdisciplinary dialogue. It is concluded that the use of legal means and techniques to combat marginality is based on the hypothesis of legal consciousness, according to which anyone initially focuses on consciousness, socially active and useful, and therefore on lawful behavior established by law. This approach can be formed, strengthened, or restored through the implementation of educational, ideological, and other functions of law, political science, or history.